The 12-th Scientific Session of the Mathematical Commission of the T. H. Shevchenko Scientific Society - Samoilenko, A.M.; Prytula, M.M. (Нелінійні коливання, 2001)
A session of the mathematical commission of the T.H. Shevchenko Scientific Society (SSS)
was held on March 16 – 17, 2001 at the I. Franko L’viv National University. The session was organized both by the mathematical commission of the T. H. Shevchenko Scientific Society and the L’viv National University.